2012
DOI: 10.1186/1471-230x-12-144
|View full text |Cite
|
Sign up to set email alerts
|

The optimal screening interval for gastric cancer using esophago-gastro-duodenoscopy in Japan

Abstract: BackgroundGastric cancer is one of the most significant diseases, and esophago-gastro-duodenoscopy (EGD) is one of screening methods for gastric cancer. This study was conducted to identify the optimal screening interval for gastric cancer using EGD in healthy adults.MethodsA retrospective cohort study was conducted on 3,723 healthy participants without a known diagnosis of gastric cancer at baseline from January 2005 to December 2010. Participants underwent annual health screenings, including EGD, at the Cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…One study on EGD screening for the general Japanese population showed a 0.8% overall 5‐year cumulative incidence rate of gastric cancer, 17 and the present study indicated relatively higher incidence rates of remnant gastric cancer after gastrectomy. Our analyses identified a Brinkman index ≥ 600, proximal gastrectomy, and tumor size ≥ 30 mm as risk factors for remnant gastric cancer.…”
Section: Discussionsupporting
confidence: 64%
“…One study on EGD screening for the general Japanese population showed a 0.8% overall 5‐year cumulative incidence rate of gastric cancer, 17 and the present study indicated relatively higher incidence rates of remnant gastric cancer after gastrectomy. Our analyses identified a Brinkman index ≥ 600, proximal gastrectomy, and tumor size ≥ 30 mm as risk factors for remnant gastric cancer.…”
Section: Discussionsupporting
confidence: 64%
“…In general, increased age is an important risk factor for development of gastric cancer. Over 50 years old, the risk for incidence of gastric cancer is increased approximately two times and cumulative incidence of gastric cancer is increased with increased age . Yuji and colleagues reported that the risk of metachronous gastric cancer incidence was increased in the proportion of more than 5‐year follow‐up duration, regardless of the presence of H. pylori .…”
Section: Discussionmentioning
confidence: 99%
“…Studies of gastric cancer screening time interval, Korea research (Kim et al, 2000) proposals for 1-5 years, the optimal time interval should be less than 3 years; Singapore (Dan et al, 2006) recommends every two years for a screening for gastric cancer; Japanese people aged 60-69 is recommended once every 2 to 3 years, and 50 to 59, once every four years, less than 50, but once every five years or more (Kobayashi et al, 2012). No gastric cancer screening interval research of our country, it can be used as our further research.…”
Section: Discussionmentioning
confidence: 99%